Construction of Multicolor Upconversion Nanotheranostic Agent for in-situ Cooperative Photodynamic Therapy for Deep-Seated Malignant Tumors - Hong, Tongtong; Jiang, Yanxialei; Yue, Zihong; Song, Xinyue; Wang, Zonghua; Zhang, Shusheng (Frontiers in Chemistry, 2020)
Upconversion nanoparticles (UCNPs)-based photodynamic nanotheranostic agents could address the main drawbacks of photosensitizer molecules (PSs) including instability in aqueous solution and rapid clearance. Due to the relatively weak luminescence intensity of UCNPs and insufficient reactive oxygen species (ROSs), UCNPs-based photodynamic therapy (UCNPs-PDT) was discounted for deep-seated tumors. Thus, we proposed a PSs-modulated sensitizing switch strategy. Indocyanine green (ICG) as an NIR organic dye was proved to effectively enhance the luminescence intensity of UCNPs. Herein, four-color UCNPs were coated with a silica layer which loaded ICG and PSs while the thickness of silica layer was controlled to assist the sensitization function of ICG and activation of PSs. Under the drive of mitochondria-targeting ligand, the prepared nanotheranostic agent would accumulate in the mitochondria where ROSs were in-situ produced and then cell apoptosis was induced. Due to the cooperative PDT and high tissue-penetration depth of NIR laser, the prepared upconversion nanotheranostic agent could achieve significant inhibition on the deep-seated tumors.